Analysing the impacts of closure of a military base using a dynamic CGE model - Bayar, Ali (2018)
Military bases are commonplace in many countries and may have a significant impact in the communities where they are integrated. Impacts of military bases have been analysed through different perspectives. Our aim is to analyse their economic impact. The importance of military bases has become a topic of discussion particularly when base closures or base activity reductions are under consideration. In a previous paper the authors looked at the issue using a static CGE model applied to the analysis of the economic impact of a US base located in the island of Terceira in the Azores. In the current paper a dynamic model is used to study the same issue, using more recent data and disaggregating the impact among different household categories. A base closure scenario is created and the impacts traced through various economic indicators. It is concluded that GDP falls, relative to the base scenario for a number of years recovering after some time, assuming that worsened trade balances are compensated by other transfers. This fall is prompted by a fall in employment, personal income and consumption. The model also predicts that the impact hurts different household income groups with diverse intensity. Lower income households are hurt more in relative terms but generate a smaller absolute impact. With time, the negative impact tapers off for most income groups except for the lowest which keeps on loosing more until the end of the simulation period.